Relación entre satisfacción laboral y compromiso organizacional en profesionales - Bailetti Barreto, Luciana (2022)
In the last few years, organizations have experienced great difficulties in retaining their staff, which has been reflected in high rates of employee turnover. The aim of this study was to analyze the relationship between job satisfaction and organizational commitment of employees and the impact it has on the turnover rates of companies from different industries. A systematic review was carried out based on the criteria mentioned in the PRISMA guideline (Page et al., 2021) in the EBSCOhost and Proquest databases. Studies that presents significant statistics that correlate job satisfaction and organizational commitment were selected (n=10). The results showed a direct and significantly positive relationship between job satisfaction and organizational commitment, as well as predictive relationships between both variables. In addition, both variables showed a significant impact on the desire of employees to stay or leave their company, so it is concluded that both are directly related to organizational turnover rates. Human Resources plays a fundamental role in promoting measures focused on generating a satisfactory experience that encourages the employee's desire to stay in the company.